2019
DOI: 10.3390/su11195185
|View full text |Cite
|
Sign up to set email alerts
|

A Double Hurdle Estimation of Sales Decisions by Smallholder Beef Cattle Farmers in Eswatini

Abstract: Beef cattle farmers are in an ideal position to advance their income through marketing; however, the subsector is characterized by low market participation. Wealth preservation and prestige from cattle accumulation outweigh market incentives, thereby jeopardizing the integration of farmers into organized market systems. Therefore, the study was set to examine the determinants of farmers’ sales decisions in cattle marketing. Understanding determinants of sales decisions is an indispensable base for establishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
4
32
0
Order By: Relevance
“…Access to farm credits should be improved among pastoralists. Farm credit is important for investing in beef cattle production, thus boosting beef cattle productivity and profitability, which improves the economic sustainability of beef cattle production [32]. Regarding access to veterinary services, results show that 56.3% of pastoralists had access to veterinary services.…”
Section: ( ) = (8)mentioning
confidence: 99%
“…Access to farm credits should be improved among pastoralists. Farm credit is important for investing in beef cattle production, thus boosting beef cattle productivity and profitability, which improves the economic sustainability of beef cattle production [32]. Regarding access to veterinary services, results show that 56.3% of pastoralists had access to veterinary services.…”
Section: ( ) = (8)mentioning
confidence: 99%
“…Agribusiness management practices are paramount in the organization of production efforts and the transaction of marketable surplus. Knowledge and skills in agribusiness and cattle marketing and pricing are key in enhancing farmers' competitiveness in the unorganized market structure in Eswatini [50]. This is vital in increasing the economic benefit that creates interest in agribusiness farming.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…Market imperfection, induced by the lack of an organized cattle market structure [50], has deprived farmers of market price information, hence the low competence levels in cattle marketing and pricing. The insignificant difference between the gender groups regarding cooperative and farm business management is logical since such practices are not embedded in the traditional farming system that serves as the basis for household farm education.…”
Section: Proficiency In Production and Agribusiness Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies used this model as a tool for the second stage because the efficiency score of farms calculated in the first stage ranged from 0 to 1 and had censored distributions [37]. However, recent studies also showed that there exists an inadequacy in the result of the Tobit model due to the biased estimation [38]. Hence, the truncated regression model is a more appropriate choice to explain the relationship between environmental efficiency score and independent variables related to the socioeconomic characteristics of edible canna farms.…”
Section: Truncated Regression Modelmentioning
confidence: 99%